Mirrors and prisms interrogating accounting - Lehman, Cheryl R. (Emerald, 2002)
This research publication has two major aims. First, to provide a forum for researchers concerned with critically appraising and significantly transforming conventional accounting theory, practice, teaching and research. Second, to increase the social self-awareness of accounting practitioners, educators, and researchers, encouraging them to assume a greater responsibility for the profession's social role. With chapters on topics as wide as gender, ethnicity and demographic factors influencing promotions to managers for auditors, and auditors' compliance with employment eligibility verification, this collection features papers by leading academics from both sides of the Atlantic and beyond.
Keywords: Social accounting.; elektronické knihy; electronic books